Decadal temperature changes in the Tasman Sea - Philip J.H. Sutton; Melissa Bowen; Dean Roemmich (New Zealand Journal of Marine and Freshwater Research, 2005)
Ocean temperature changes between 1991 and 2005 in the eastern Tasman Sea were analysed. This area was chosen because of a combination of data availability, low mesoscale variability and because of its importance in determining the climate of the downwind New Zealand landmass. A large warming extending to the full depth of the water column (c. 800 m) was found to have occurred between 1996 and 2002. This warming was seen in measurements by expendable bathythermographs and also in satellite sea surface temperature and sea surface height products, and has a clear impact on New Zealand's terrestrial temperature. The nature of the warming is discussed, together with likely forcing mechanisms. No local forcing mechanisms are consistent with the observed warming, leading to the conclusion that the signal seen in the Tasman Sea is part of a larger South Pacific‐wide phenomenon.